The Effect of The Application of Play Therapy On The Anxiety Level of Children Experiencing Hospitalization Reactions In Pre-School Age Children At Rsud Haji Provinsi Sulawesi Selatan - Harnilawati; Asrianto (International Journal of Science, Technology & Management, 2021)
When hospitalized, children have to be left behind by their loved ones, family and friends that it causes anxiety to the children. In addition to anxiety caused by separation, children can also experience anxiety due to losing control of themselves. The implementation of Play Therapy is part of child care and one of the effective interventions for children. The purpose of the study is to determine the effect of the application of Play Therapy on reducing anxiety in pre-school age children at RSUD Haji Provinsi Sulawesi Selatan. The research method used was Quasy experiment with a pre-test and post-test control group approach. The subjects in this study were pre-schoolers with a total sample of 40 people consisting of 20 people in the treatment group and 20 people in the control group with the determination of the sample using consecutive sampling. The instrument used to measure the level of anxiety was the Hamilton Anxiety Rating Scale (HARS), while the intervention was in the form of Play Therapy, especially drawing and coloring games. The results showed that the Wilcoxon Signed Rank Test statistical test in the treatment group obtains a significant value of p = 0.000, smaller than ? = 0.05, which means that there are differences in anxiety levels from the results of the pre-test and post-test. Meanwhile, in the control group, a significant value of p = 0.480 is obtained, which is greater than ?= 0.05, meaning that there is no difference in the level of anxiety from the results of the pre-test and post-test.